2007
DOI: 10.1369/jhc.7a7188.2007
|View full text |Cite
|
Sign up to set email alerts
|

Septin Expression in Proliferative Retinal Membranes

Abstract: S U M M A R Y We undertook this study to evaluate the expression of septin family members SEPT5, SEPT8, and SEPT11 in proliferative retinal membranes. Epiretinal membranes (ERM) were obtained from seven patients with proliferative vitreoretinopathy (PVR) and from four patients and four postmortem eyes with proliferative diabetic retinopathy (PDR). Subretinal membranes (SRM) were obtained from one patient and six postmortem eyes. Membranes were examined by immunohistochemical staining of paraffin sections using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Furthermore, in contrast to sept3 and sept5b , no sept5a expression is detectable in the retina at 4 dpf. The observed expression of sept5b in the zebrafish retina is in accordance with immunohistochemistry studies of SEPT5 in human eye tissues (Pache et al, 2005 ; Xin et al, 2007 ), which suggests an important conserved role of Sept5 in retinal development (Xin et al, 2007 ). The sept5b expression differs from the expression of sept3 in the retina.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, in contrast to sept3 and sept5b , no sept5a expression is detectable in the retina at 4 dpf. The observed expression of sept5b in the zebrafish retina is in accordance with immunohistochemistry studies of SEPT5 in human eye tissues (Pache et al, 2005 ; Xin et al, 2007 ), which suggests an important conserved role of Sept5 in retinal development (Xin et al, 2007 ). The sept5b expression differs from the expression of sept3 in the retina.…”
Section: Discussionsupporting
confidence: 82%
“…Studies of mammalian septins have been primarily focused on their association with cancer and neurological diseases. However, many other interesting functions are coming to light such as the role of certain septins in bacterial infection (44)(45)(46), angiogenesis (72), spermatogenesis (40)(41)(42)(43)101), retinal degeneration (102,103), platelet release reaction (32)(33)(34)(35)104), and beyond. Still, questions related to their normal function in cells and to their implication in human diseases are still puzzling.…”
Section: Resultsmentioning
confidence: 99%
“…Higher expression of Olfactory receptor, SEPTIN5 in transgenic cattle may strengthen the function of olfactory sense, visual sense respectively [ 76 , 77 ]. Suh M had demonstrated that fat-1 mice enriched highly ω-3 fatty acids in the retina lead to supernormal scotopic and photopic ERGs and increases in Muller cell reactivity and oxidative stress in photoreceptors [ 78 ].…”
Section: Results and Analysismentioning
confidence: 99%